Simulation study of gasification of empty fruit bunch (EFB) for electricity generation using Superpro designer - Shariffudin, Muhammad Syazwan; Abdul Jalal, Nurfatin Azma; Mel, Maizirwan; Sulaiman, Sarina; Ihsan, Sany Izan; Wae-Hayee, Makatar (Kulliyyah of Engineering, IIUM, 2022)
Energy generation using non- renewable sources has always been an issue to the environment. To sustain the environment, gasification process using biomass as carbonaceous fuel is urged to reduce the dependency on coal or fossil fuel as the feed to generate energy. This project focused on identifying the best condition for running a gasification process using SuperPro Designer v9.5 software. The software was used to design the power plant by having the required unit operations such as gasification, cyclone separator, cooling, absorption, gas compression and gas expansion in their library. The unit operations were then arranged to build the plant and optimized by using Minitab v14 software to find out the best condition among the selected factors which are the fuel, steam, and oxidant streams into the gasifier for producing high yield of electrical energy. The result demonstrated that the biomass feed stream of two metric tons per hour of empty fruit bunch (EFB), one metric ton per hour of steam feed and zero-point five metric ton of air were enough to generate about 8246 kWh of electricity. Overall, all runs showed a good and approximately equal performance which indicate that the SuperPro designer simulation is reliable for analyzing gasification performance.